DWELLING IN-BETWEEN US AND ALTERED REALITIES: TIME STANDS STILL - Quadros, Tomé Saldanha; Pinto, Joana (Design/Arts/Culture, 2026)
From Aristotle to Bazin, the concept of art as mirror to reflect reality and the ontological level that establishes an existential relationship between image and reality respectively, depicting space, time and causality, is still today subject of constantly evolving. At the turn of the twenty-first century, understood as pictorial turn or Age of simulation (W. J. T. Mitchell, 1992), or even Age of disposable people (Rey Chow, 2010), the contribution of moving images to collective and individual memory relies, precisely, on questioning its boundaries when relating to visual literacy (James Elkins, 2008). The landscape of memory coming to fruition, dwelling in-between staged and altered realities, creates, then, the illusion of transparency as a catalyst to provoke re-actions. By evoking and questioning mediation as “creator’s essence” towards the vision of the “world as a picture”, “Entre Nós” (Between Us, 2025) emerged from artistic disquite. Namely, the need to seek challenges, in particular the continuous looking forward to discover an idea as we tried to merge the expectations of everyone. Last but not least, the urgency to materialize it within a limited time-frame. The opportunity of developing this project arose at a moment of closure, when seizing every opportunity became essential. Above all, it came about the eagerness to start building a meaningful path for us as artists.